IMPLEMENTATION OF BIOMIMETIC ARCHITECTURAL CONCEPTS ON EQUESTRIAN BUILDINGS - Fadhurrahman, Farhan; Mutia, Fairuz (ADBE, 2021)
Equestrian sport is one of the efforts to improve human resources and quality. To create good conditions for athletes and the horses themselves, it is therefore necessary to have an open space that is environmentally responsive by making this place their ’home’. To create an open and environmentally responsive space, this equestrian building will use the concept of Biomimetic Architecture, the concept of Biomimetic Architecture to obtain the basic concept of architectural design that minimizes changes to the site. Biomimetic architecture uses nature as a model, reference and guide for solving problems in architecture. This research aims to analyze the points of biomimetic architecture that can be applied to buildings. This research is included in the descriptive qualitative category, especially using synchronic analysis which produces a solution in the form of a design concept. Data collection is obtained from the literature study which is then synthesized and becomes design criteria. From each application point studied, it can answer problems regarding the effect of each criterion on the building itself.